Syntheses of bis(pyrrolylaldiminato)aluminum complexes for the polymerisation of lactide - Supathana Pracha (2018)
Seven bis(pyrrolylaldiminato)aluminum methyl complexes were synthesized from the reactions of AlMe3and two equiv. of the corresponding pyrrolylaldimine ligands. The ligands were modified to have different steric hindrances (C6H5(1), 2,6-Me2C6H3(2), 2,4,6-Me3C6H2(3), 2,6-Et2C6H3(4) and 2,6-iPr2C6H3(5)) and electronic contributions (4-CF3C6H4(6) and 4-OMeC6H4(7)). Crystal structures of complexes 3-7 were determined and shown to have distorted trigonal bipyramidal geometry (4, 6, 7) and intermediates between trigonal bipyramidal and square pyramidal geometries (3 and 5). The rotation around the N-Carylbond was fast for ligands having small ortho substituents and became slower as the size of the substituents increased. Polymerisations of l-lactide using complexes 1-7 and benzyl alcohol as an initiator were carried out giving the rate dependence on steric hindrance (5 < 4 < 3 < 2 < 1) and electronic contribution (6 < 7 < 1). Larger substituents and electron withdrawing groups were found to suppress the polymerisation rates. Despite having C2symmetry in the crystal structures of compounds 3-7, only slight enhancement for isotactic enchainment was found in the polymerisation of rac-lactide. © 2013 The Royal Society of Chemistry.